Evaluating the feasibility of ReWork-SCI: a person-centred intervention for return-to-work after spinal cord injury - Susanne Guidetti; Eric Asaba; Lisa Holmlund; Claes Hultling; Åke Seiger; Gunilla Eriksson (BMJ Open)
Objectives To evaluate the feasibility of: (1) ReWork-SCI with regard to adherence and acceptability and (2) a study design for evaluating ReWork-SCI with regard to recruitment, retention and outcome measures.Design Pre-test and post-test, single group, feasibility study.Setting Spinal cord injury (SCI) unit at a regional rehabilitation centre in Sweden.Participants Two women and five men (n=7). Eligible criteria: (1) sustained traumatic or non-traumatic SCI; (2) completed the first acute care episode in a hospital; (3) between 18 to 65 years of age; (4) assessed by a physician as approachable for participation in the intervention; (5) history of permanent or temporary employment; (6) self-reported desire to return to work; and (7) ability to communicate in English or Swedish.Intervention ReWork-SCI is a person-centred intervention for return-to-work (RTW), developed and evaluated using the Medical Research Council’s guidelines. ReWork-SCI follows a person-centred, structured and coordinated intervention process led by a coordinator within a SCI rehabilitation team.Outcome measures The feasibility of ReWork-SCI and a study design was evaluated using a set of outcome measurement tools, vocational data, logbooks and semi-structured interviews.Results All eligible participants accepted enrolment and follow-up. All participants had a plan for RTW after 3 months and four participants had initiated part-time work or work trial 6 months after commencement of intervention. Adherence and acceptability were overall good. Challenges of the intervention related to the person-centred follow-up, staff shortage and rootedness in the SCI team.Conclusions ReWork-SCI was feasible and can contribute to a systematic design of an individualised plan, facilitate decision-making and build trust in the RTW process after SCI. Core features of the intervention was the systematic structure, use of a person-centred approach and dialogue with the employer. For the effectiveness of ReWork-SCI, modifications and considerations of study design are needed.